Answer: x = - 7/12
Step-by-step explanation:
-3x + 2 - 5x - 7 = 4x + 2
=> -8x - 5 = 4x + 2
=> -12x = 7
=> x = - 7/12
Sophie is correct because 295 + 65 = 360 and 360 is the # of degrees in a full circle
Step-by-step explanation:
Given equations:
y = x² + 3x - 29 ------ (i)
y = 2x - 9 ---------------- (ii)
Now to solve this problem, we must determine the value of x and y;
Equate equations 1 and 2;
x² + 3x - 29 = 2x - 9
x² + 3x - 2x - 29 + 9 = 0
x² + x - 20 = 0
x² + 5x - 4x - 20 = 0
x(x + 5 ) - 4(x + 5) = 0
(x - 4) (x+ 5) = 0
x - 4 = 0 or x + 5 = 0
x = 4 or x = -5;
So; solve for y now;
y = 2x - 9
input x = 4 or x = -5;
y = 2(4) - 9 or y = 2(-5) - 9
y = -1 or y = -19
Answer:
Multiply both sides by -2 and reverse the inequality symbol
Step-by-step explanation:
since it is division you want to make it multiplication so that you can get the answer easier
-1/2w<12
it cancels out the -1/2 than just multiply 12 and -2 you get -24
w > -24
Answer:
3) f(x) = 3(x + 2)^2 - 1.
Step-by-step explanation:
f(x) = 3x² + 12x +11
f(x) = 3(x^2 + 4x) + 11 Completing the square:
f(x) = 3[(x + 2)^2 - 4] + 11
f(x) = 3(x + 2)^2 -+3*-4 + 11
f(x) = 3(x + 2)^2 - 12 + 11
f(x) = 3(x + 2)^2 - 1.